KOMPARASI MODEL PEMBELAJARAAN KOOPERATIF TIPE MAKE A MATCH DAN TIPE TEAM GAMES TOURNAMENT (TGT) PADA MATERI KONSEP MOL TERHADAP HASIL BELAJAR SISWA KELAS X SMA KARTIKA XIII-1 AMBON - Marlifia Berhitu; Semuel Unwakoly; Y Manoppo (Molluca Journal of Chemistry Education (MJoCE), 2019)
The purpose of this research is to know thestudent learningoutcomes of grade X SMA KARTIKA XIII-1 AMBON as well as knowing there is a difference whether or not the results of student learning using cooperative type Team Games Tournament(TGT) with type Make a Match as the learning model.This research is the comparison research which the sample consists of two classes, the class was given further study of chemistry at the consept of moles materials, first classexperiment (X-1) using the cooperative type Team Games Tournament(TGT) and in secondclass experiment (X-2) using the cooperative type Make a Match as the learning model. Based on the results of the study gained note that both models of learning that can enhance the learning outcomes of students, it can be seen from the success of the qualifications obtained from both the class when there has same qualification of 75% of students are on completed qualifying, 25% of students are on failed qualifying, with average from X-1 class used Type TGT is 66.125 and X-2 class used Type Make a Match is 57.3125. Hypothesis test data derived from posttest both class indicates the value significance of 0.25 (> 0.05) this a value of H0received and value of H1 rejected so it can be concluded there is no difference in student learning outcomes are either the cooperative type Team Games Tournament (TGT)and type Make a Match as the learning model.